2019
DOI: 10.1093/aje/kwz079
|View full text |Cite
|
Sign up to set email alerts
|

Invited Commentary: The Causal Association Between Obesity and Stillbirth—Strengths and Limitations of the Consecutive-Pregnancies Approach

Abstract: There has been a resurgence in analyses of consecutive pregnancies (or similarly, sibling designs) in perinatal and pediatric epidemiology. These approaches have attractive qualities for estimating associations with complex multifactorial exposures like obesity. In an article appearing in this issue of the Journal, Yu et al. (Am J Epidemiol. 2019;188(7):1328–1336) apply a consecutive-pregnancies approach to characterize the risk of stillbirth among women who develop obesity between pregnancies (“incident obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…We note that incident obesity due to interpregnancy weight gain may reflect a shorter duration of exposure to mechanisms like inflammation or metabolic dysfunction than that experienced by individuals with established, long-term obesity. (31) Mechanisms for associations between low BMI and SMM are unclear. In a prior mediation analysis, we reported that the association between prepregnancy obesity and SMM was explained by accounting for comorbidities and cesarean delivery, but these mediators did not affect the association between low BMI and SMM, suggesting different pathways.…”
Section: Discussionmentioning
confidence: 99%
“…We note that incident obesity due to interpregnancy weight gain may reflect a shorter duration of exposure to mechanisms like inflammation or metabolic dysfunction than that experienced by individuals with established, long-term obesity. (31) Mechanisms for associations between low BMI and SMM are unclear. In a prior mediation analysis, we reported that the association between prepregnancy obesity and SMM was explained by accounting for comorbidities and cesarean delivery, but these mediators did not affect the association between low BMI and SMM, suggesting different pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In doing so, they broach an issue that is omnipresent in perinatal epidemiology: recurrent pregnancy outcomes. Whether across a woman's pregnancies or across generations, information on a past pregnancy outcome is often helpful for understanding the present 2 . But how, specifically, should this information be used?…”
Section: Introductionmentioning
confidence: 99%
“…Whether across a woman's pregnancies or across generations, information on a past pregnancy outcome is often helpful for understanding the present. 2 But how, specifically, should this information be used? There is relatively little guidance on the unique considerations of formulating research questions related to recurrent outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…We thank Drs. Snowden and Leonard (1) for elaborating on the generalizability of our results on the relationship between incident obesity and stillbirth (2). To quantify the association between incident obesity and stillbirth, we restricted our analyses to women who were not obese at the time of their first pregnancy.…”
mentioning
confidence: 99%